Flows of Literacy across Corporate and User-Produced Virtual Worlds. Issue 12 (November 2017) - Black, Rebecca W.; Alexander, Jonathan; Korobkova, Ksenia A.
Background/Context: Sociocultural research on young people's literate practices with digital media has generally focused on literacy events and practices that are grounded in distinct online locations, such as affinity spaces, specific websites, particular videogames, or virtual worlds. Purpose/Objective/Research Question/Focus of Study: Contemporary media landscapes have become networked to such an extent that a transmedial approach is needed to understand the social, cultural, and literate contexts that young people inhabit. Research Design: In this article, we use qualitative and literary analyses of products and artifacts from the Hunger Games media franchise to explore young people's literacy practices as embedded in corporate and fan-produced transmedia ecologies. Conclusions/Recommendations: Our analysis looks beyond spatial and structural boundaries to understand how flows of corporate and user-produced artifacts can shape, constrain, and expand young people's literate repertoires.